Thermal convection in a binary fluid saturated an anisotropic porous medium with nonlinear temperature profile - Abdul Hamid, Nur Zarifah (2019)
In this thesis, the thermal instability in a binary fluid layer saturated an anisotropic porous medium in the presence of nonlinear temperature profile is formulated mathematically based on Darcy’s model and Boussinesq approximation. The linear stability analysis is applied to the system and the resulting eigenvalue obtained are solved numerically using single-term Galerkin method with respect to lower rigid and upper free conducting boundary and lower rigid conducting and upper free insulating boundary. Several effects are considered in this study, which include the effect of nonlinear temperature profile, anisotropic parameter, binary fluid parameter, internal heat generation, magnetic field and feedback control in order to test the stability of the system. The onset of convection is the most advance in the presence of cooling from above temperature profile while the system is the most stable in the presence of cubic 1 temperature profile. The results obtained are drawn graphically and showed similarities with the result obtained by previous research.